INVESTIGATING READINESS ATTITUDE TOWARD USING MOBILE PAYMENT SYSTEMS THROUGH TECHNOLOGY ACCEPTANCE MODEL - Asrul Sani; Nur Nawaningtyas Pusparini; Agus Budiyantara; Irwansyah Irwansyah; Anton Hindardjo (Kresnamedia Publisher, 2021)
Abstract The development of mobile payments is in line with the increasing number of application developers making features that are easy to use. The readiness of users to use mobile payments in making transactions is the main thing, whether users trust the applications used in transactions. This study attempts to model a framework where the technology readiness index and the technology acceptance model are used. Respondents in the study were in Jakarta with a purposive sampling technique, amounting to 204. Data processing used SPSS and SmartPls 3.0 applications. The results of this study provide knowledge about the level of readiness in using the mobile payment application, giving rise to an attitude of optimism, but not from a security perspective. Users still feel that mobile payments are still not safe to make transactions online.